JENIS-JENIS TANAMAN DI LAHAN GARAPAN PETANI KPPH WANA MAKMUR DALAM TAHURA WAN ABDUL RACHMAN - Agung Dwi Prasetyo; Indriyanto Indriyanto; Melya Riniarti (Universitas Lambung Mangkurat, 2019)
The increasing needs and the nearness residential distance from the forest were several factors that caused society to do the utilization of the forest land. Sungai Langka village was a village directly adjacent to the Wan Abdul Rachman great forest park area, where most societies were farmers who manage the land inside the Wan Abdul Rachman great forest park area. The objective of this research i.e.: 1) To find out the species of plants cultivated by farmers on the land-based on habitus, plant groups, and commodities produced; 2) to count the density of each plant group; 3) to find out the most plants as a source of farmers incomes. This research was conducted with a vegetation survey using the terraced line method. The number of sample plots used was 69 pieces measuring 20m x 20m, 10m x 10m, 5m x 5m, and 2m x 2m. The results of the study showed that there were 35 plants species on farmers cultivated land which is dominated by plants of the forest group MPTS with a density of 3,637.66 individuals/ha, forest wood plant 797,83 individuals/ha, agricultural MPTS 2,294.2 individuals/ha, and agricultural crops 1,533.34 individuals / ha. Therefore, could be concluded that most of the plants on arable land were fruit-producing plants which were partially included in the MPTS forest group plants, and farmers rely on crops such as cocoa, banana, durian, clove, nutmeg, rubber, petai, pepper and vanilla as the source of income and fulfill their needs.